هێمای زمانیی و نازمانیی لە چوارچێوەی سیمانتیک و پڕاگماتیکدا - حسێن, پ.ی.د. جوانە ئەحمەد حەمە; عەلی, خوێندکار: م. فەرەیدون عەبدوڵڵا (Sulaimani Journal for Humanities, 2023)
This research is titled as (Linguistic and Nonlinguistic symbols in semantic and pragmatic) context. It is an attempt to analyze and interpret the meaning of linguistic and nonlinguistic symbols that carry different meanings which we use in our daily life. Language simply is a structure that contains a string of words and a bunch of meaning; throughout this category we can keep the continuity of life interchange and understanding. Language has its own rules that carry the characteristics of the language. that is, each language on several principles expand the culture of the language and the culture of the speakers, that are ability and power which is expressed through linguistic and nonlinguistic symbols. Linguistics is the science of language which consists of (theoretical and practical) categories. Most of the research includes these two categories, but semiology was less included. This research is essentially a theoretical and practical part of a master`s degree that must be published as part of the requirements for obtaining a master`s degree. It tries to interpret the meaning of linguistic and non-linguistic symbols in semantic and pragmatic terms. The scope of the research is about our daily life interchangeability we do in a Kurmanji accent.
Keywords: (هێمای زمانیی هێمای نازمانیی واتای سیمانتیکی واتای پڕاگماتیکی کۆد هێمالۆژی تیۆری دەوروبەر وێنەی کاریکاتێر)